FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ASFIKSIA NEONATORUM DI RUANG MELATI RSUD Dr.H.SOEWONDO KENDAL - Wulandari, Priharyanti; Arifianto, Arifianto; Senjani, Fessa Puji (Universitas Muhammadiyah Magelang, 2016)
Background :Asphyxia neonatorum is a state where the the newborn baby is not able tobreathe spontaneously and regularly after birth. Factors that influence the incidence of asphxia neonatorum maternal Age, gestational age, parity, the distance the weight of pregnancy, the baby is born (BBL). The purpose of this research is to know the factors associated with the incidence of asphyxia neonatorum in the jasmine room at Dr. H. Soewondo Kendal hospital. Methods : this study is a kind of correlation approach to research retrospective. The population of the study all infants who suffered asphxia of jasmine in the room as much as 377. Using the technique of sampling a total aside. Results : the results of the statistical test of Chi-Square, the relationship between age of asphxia neonatorum with moms in mind r-Value of 0,000 (< 0,05), the relationship between age of pregnancy asphyxia neonatorum with know r-Value of 0,000 (< 0,05), the relationship between asphyxia neonatorum with parity known r-Value of 0,000 (< 0,05), the relation between distance of pregnancy with asphyxia neonatorum r-Value of 0,000 (< 0,05), the relationsip between asphyxia neonatorum with BBL known r-Value of 0,000 (< 0,05). Conclusion : there is a relationship between the mother’s Age, gestational age, parity, the distance the weight of pregnancy, the baby is born (BBL) with asphyxia neonatorum in the jasmine room at Dr. H. Soewondo Kendal hospital.